Pengaruh Pengungkapan Informasi Keuangan terhadap Keputusan Investasi (Studi Empiris pada Perusahaan yang Terdaftar di Indeks Kompas Periode 2023) - Sari, Amilia Paramita (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aims of this study are to gather empirical evidence on the impact of financial information on investment decisions involving abnormal share returns, as well as evidence of the occurrence of abnormal share returns during financial information publication, and to distinguish between abnormal share returns occurring before and after the publication of the financial information by the company. As a sample for this study, there will be 63 companies included in the Compass 100 Index by 2023. A Wilcoxon rating test, a sample t test, and simple regression are used to test three research hypotheses. The findings of this study suggest that investment decisions are not affected by the level of disclosure of corporate financial information. However, this study also shows abnormal stocks. This study shows that abnormal stock returns before and after the publication of financial information by the company are different.